2000
DOI: 10.1152/physiolgenomics.2000.4.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid receptor-β: an endogenous inhibitor of the perinatal formation of pulmonary alveoli

Abstract: Pulmonary alveoli are formed, in part, by subdivision (septation) of the gas-exchange saccules of the immature lung. Septation is developmentally regulated, and failure to septate at the appropriate time is not followed by delayed spontaneous septation. We report retinoic acid receptor (RAR) beta knockout mice exhibit premature septation; in addition, they form alveoli twice as fast as wild-type mice during the period of septation but at the same rate as wild-type mice thereafter. Consistent with the perinatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 33 publications
2
72
0
1
Order By: Relevance
“…Until recently, no abnormal lung phenotype had been 388 associated with deletion of any of these genes (8,10,27). However, others have shown that simultaneous deletion of RAR␣ and RAR␤ produces pulmonary hypogenesis or agenesis, which is usually unilateral (28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Until recently, no abnormal lung phenotype had been 388 associated with deletion of any of these genes (8,10,27). However, others have shown that simultaneous deletion of RAR␣ and RAR␤ produces pulmonary hypogenesis or agenesis, which is usually unilateral (28).…”
Section: Discussionmentioning
confidence: 99%
“…The lungs then were filled through the trachea with 2% paraformaldehyde at 20 cm H 2 O pressure and were maintained at this pressure for 18 h at 4°C. This inflation pressure has been used in previous studies describing the influence of retinoids on alveolarization (4,5,10). The lungs were monitored for leakage during this procedure, and only lungs that did not leak were used for further study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in RAR mutant mice suggest that RA can act as a positive or a negative regulator of alveolization depending on the RAR type. RARb-null mice septate earlier and faster than control mice, whereas RARg null have decreased alveolar number and an increase in alveolar volume (40,41).…”
Section: Retinoic Acid From Buds To Alveoli: a Role In Lung Repair Anmentioning
confidence: 95%